Plasmalogens Inhibit APP Processing by Directly Affecting γ-Secretase Activity in Alzheimer’s Disease - Tatjana L. Rothhaar; Sven Grösgen; Viola J. Haupenthal; Verena K. Burg; Benjamin Hundsdörfer; Janine Mett; Matthias Riemenschneider; Heike S. Grimm; Tobias Hartmann; Marcus O. W. Grimm (The Scientific World Journal)
Lipids play an important role as risk or protective factors in Alzheimer’s disease (AD). Previously it has been shown that plasmalogens, the major brain phospholipids, are altered in AD. However, it remained unclear whether plasmalogens themselves are able to modulate amyloid precursor protein (APP) processing or if the reduced plasmalogen level is a consequence of AD. Here we identify the plasmalogens which are altered in human AD postmortem brains and investigate their impact on APP processing resulting in Aβ production. All tested plasmalogen species showed a reduction in γ-secretase activity whereas β- and α-secretase activity mainly remained unchanged. Plasmalogens directly affected γ-secretase activity, protein and RNA level of the secretases were unaffected, pointing towards a direct influence of plasmalogens on γ-secretase activity. Plasmalogens were also able to decrease γ-secretase activity in human postmortem AD brains emphasizing the impact of plasmalogens in AD. In summary our findings show that decreased plasmalogen levels are not only a consequence of AD but that plasmalogens also decrease APP processing by directly affecting γ-secretase activity, resulting in a vicious cycle: Aβ reduces plasmalogen levels and reduced plasmalogen levels directly increase γ-secretase activity leading to an even stronger production of Aβ peptides.